2021
DOI: 10.1186/s13058-020-01377-5
|View full text |Cite
|
Sign up to set email alerts
|

NRG1 fusions in breast cancer

Abstract: Background NRG1 gene fusions may be clinically actionable, since cancers carrying the fusion transcripts can be sensitive to tyrosine kinase inhibitors. The NRG1 gene encodes ligands for the HER2(ERBB2)-ERBB3 heterodimeric receptor tyrosine kinase, and the gene fusions are thought to lead to autocrine stimulation of the receptor. The NRG1 fusion expressed in the breast cancer cell line MDA-MB-175 serves as a model example of such fusions, showing the proposed autocrine loop and exceptional drug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
(113 reference statements)
0
15
0
Order By: Relevance
“…Although a recent report initially identified four cases of NRG1+ breast cancer out of 571 cases by WTS (WRN-NRG1, FAM91A1-NRG1, ARHGEF39-NRG1, and ZNF704-NRG1), further analysis of the RNA sequencing data identified only FAM91A1-NRG1 and ZNF704-NRG1 as truly in-frame, resulting in a true incidence of 0.35% (2/571) [45]. Furthermore, the same study identified 20 out of the first 250 (8%) breast cancer carcinoma samples to have a detectable DNA breakpoint within NRG1 but no RNA transcript was detected.…”
Section: Nrg1+ Breast Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Although a recent report initially identified four cases of NRG1+ breast cancer out of 571 cases by WTS (WRN-NRG1, FAM91A1-NRG1, ARHGEF39-NRG1, and ZNF704-NRG1), further analysis of the RNA sequencing data identified only FAM91A1-NRG1 and ZNF704-NRG1 as truly in-frame, resulting in a true incidence of 0.35% (2/571) [45]. Furthermore, the same study identified 20 out of the first 250 (8%) breast cancer carcinoma samples to have a detectable DNA breakpoint within NRG1 but no RNA transcript was detected.…”
Section: Nrg1+ Breast Cancermentioning
confidence: 99%
“…This DOC4-NRG1 fusion was generated by chromosomal translocation between 5′ fusion partner gene DOC4 and 3′ NRG1 gene that contains the EGF-like domain identical to the mechanism in generating the RTK fusions [1,2]. In-depth whole transcriptome sequencing (WTS) in 2021 indicated that the DOC-NRG1 fusion variant harbored a more complex rearrangement as PPP6R3-TENM4-NRG1 (PPP6R3-DOC4-NRG1) [45]. In 2003, the chromosomal breakpoints spreading over 1.1 Mb of NRG1 were identified in four additional breast cancer cell lines (ZR-75-1, HCC1937, SUM-52, UACC-812) and two pancreatic cancer cell lines (PaTu I and SUIT-2), providing further evidence that NRG1 breakpoints could be a recurring phenomenon in solid tumors [46].…”
Section: Box 1 Discovery Of Nrg1 and Nrg2 Fusions In Solid Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This theory encourages more research in the signal pathway to determine if not only inhibition of this pathway but maybe agonism can lead to tumor regression. Whether or not this is the explanation, because many NRG1 rearrangements seem to be inactivating, the correct identification of activating fusions may require care [24].…”
Section: Nrg1 and Early Reports In Cancermentioning
confidence: 99%